QUALIFICATIONS FRAMEWORK IN MODERN EDUCATION AND LABOR MARKET (Scientific electronic journal "Labor Economics and Human Capital", 2024)
The article examines the importance of qualifications in modern education and the labor market. It also highlights the role of the skills framework in supporting occupational mobility and workforce flexibility. In the scientific work, a survey was conducted and analyzed in order to determine the scope of the qualifications system for the employed population. The analysis and proposals obtained as a result of the research serve to improve the quality of education, increase the transparency of the evaluation process, ensure the variability of qualifications, and support the compliance of educational programs with the requirements of the labor market.
Keywords: Qualification framework, labor market, National Qualification System (NSS), competencies, education